Estimate the Types and Contents of Phenolic Acid in C. Parviflorus Lam and C. Salviifolius L Plants Growing at Al-Gabal Al-Khder region - Hamad Hasan,; Zaenab Habil,; Najat Ben Arous, (AlQalam Journal of Medical and Applied Sciences, 2025)
In this study, the leaves, stems, and roots of C. parviflorus Lam and C. salviifolius plants that are growing in the Al-Gabal Al-Akhder region of Libya were selected to estimate the contents and types of phenolic acids using by GCMs instrument. The study included information on chemical structure definitions and the effects of solvents. The types and contents of phenolic acid compounds and their derivatives detected in the studied samples showed small variations in their contents; some phenolic acids showed relative increases in alcoholic extracts when compared to aqueous extracts. The types and values of the phenolic compounds were dependent on the polarity of the solvents that were used in this study. In general, the types of phenolic compounds that were detected using the solvents that were used in this study are: chlorogenic acid, caffeic acid, 3,4-dihydroxybenzoic acid, 3,5-dihydroxybenzoic acid, cinnamic acid, gallic acid, geraniol, tannic acid, phloridzin, and quercetin. The phenolic acid concentration of the alcoholic and aqueous extracts varied little, according to the results.